Pengaruh Karakteristik CEO dan Aset Tidak Berwujud Terhadap Kinerja Akuisisi Dimediasi Reputasi Perusahaan¬ - Abid Ilmun Fisabil; Kamaliah Kamaliah; Rheny Afriana Hanif (Program Studi Akuntansi FPEB UPI, 2023)
The study intends to test the influence CEO characteristics and intangible assets produce on firm acquisition performance, as well as the mediating role of firm reputation. Samples were taken under purposive sampling on publicly traded firms listed on the Indonesian Stock Exchange from 2015 to 2020. SEM Path Analysis was carried out to model the research. The findings suggest a positive significant relation between CEO characteristics and firm reputation. Intangible asset, as the second independent variable, performs a significant positive relation to firm reputation. However, the study did not find any relation between CEO characteristics, intangible assets to firm performance as well as firm reputation to firm performance. In addition, the study also did not find any significant mediating role in firm performance.